1998
DOI: 10.1111/j.1469-7793.1998.245bx.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin‐1, prostaglandins and mast cells in rectal distension‐induced colonic water secretion in rats

Abstract: In vivo rectal distension (RD) induces a neurally mediated colonic net water hypersecretion in rats. Interleukin‐1β (IL‐1β) also induces neural colonic water hypersecretion involving the release of prostaglandins (PGs) and a mast cell degranulation in rats. This study investigated in vivo the role of IL‐1, PGs and mast cells in RD‐induced colonic hypersecretion. Proximal colonic net water flux was determined using [14C]polyethylene glycol (PEG) 4000 (mol. wt, 4000) in anaesthetized rats. On strips taken from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
4
11
0
Order By: Relevance
“…Our data indicate that both acute and chronic PRS similarly increase both mast cell histamine synthesis and sensitivity to SP, as shown by an increase in histamine release after SP stimulation in colonic samples of stressed rats. However, the number of mast cells was also unchanged after C‐PRS, as has previously been shown for A‐PRS 30 . This result is consistent with a previous study, 30 and suggests a modulatory role of stress on mast cell mediators, independent of stress stimuli chronicity, resulting in enhanced levels of histamine content.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicate that both acute and chronic PRS similarly increase both mast cell histamine synthesis and sensitivity to SP, as shown by an increase in histamine release after SP stimulation in colonic samples of stressed rats. However, the number of mast cells was also unchanged after C‐PRS, as has previously been shown for A‐PRS 30 . This result is consistent with a previous study, 30 and suggests a modulatory role of stress on mast cell mediators, independent of stress stimuli chronicity, resulting in enhanced levels of histamine content.…”
Section: Discussionsupporting
confidence: 91%
“…Further this group showed that peripheral administration of a mast cell stabilizer suppressed the stress-and CRF-induced hypersensitivity to rectal distension. In addition, they found that the level of histamine released from the intestines of stressed rats was significantly increased in vitro, whereas the number of mucosal mast cells was unchanged compared to the control group [85,86]. These data suggest that intestinal mast cells become more sensitive to a mast cell degranulator after stress and reinforce the hypothesis for a role of mast cells in stressinduced visceral hypersensitivity.…”
Section: Mechanisms Of Stress Effects On Gi Sensitivity In Experimentsupporting
confidence: 71%
“…These data suggest that intestinal mast cells become more sensitive to a mast cell degranulator after stress and reinforce the hypothesis for a role of mast cells in stressinduced visceral hypersensitivity. The sensitized mast cells may be responsible for the visceral hypersensitivity in response to stress through a higher synthesis and later on release of histamine and/or other mast cell mediators [85][86][87]. Despite the fact that the number of mast cells in stressed rats was unchanged compared to the control group -which is contrary to studies in IBS patients who have been shown to present more mast cells than healthy controls [88] -this idea is in agreement with neuroanatomical studies and data obtained in humans showing a close proximity of mucosal mast cells with the enteric nervous system [77].…”
Section: Mechanisms Of Stress Effects On Gi Sensitivity In Experimentmentioning
confidence: 99%
“…As an integral part of the nerveendocrine-immune network, mast cells participate in aspects of inflammation, and they also contribute to physiological regulation. Examples of the latter include the involvement of mast cells in cholecystokinin-induced disruption of the intestinal migrating motor complex (32) and in distension-induced and substance P-induced intestinal secretion (19). Some evidence attests to the importance of NT-mast cell interactions in inflammation.…”
Section: Discussionmentioning
confidence: 98%